Clinico-Epidemiological Profile and Treatment Outcome of Small Cell Lung Carcinoma: A Retrospective Study from a Tertiary Cancer Centre in Northeast India - Dutta, Chayanika; S. Roy, Partha; Mallik, Sreya; R. Daniel, Nithin (Asian Pacific Journal of Cancer Care, 2024)
Background: Small cell lung cancer (SCLC) accounts for 12-15% of all lung cancers and is associated with poor outcomes. This study aimed to understand the clinico-epidemiological profile and outcomes of SCLC in the North-East Indian population. Methods: A retrospective analysis was performed on medical records of patients with SCLC who were diagnosed, treated, and followed up at the Department of Medical Oncology, Dr. B. Borooah Cancer Institute, during the period from January 2016 to December 2021. Results: A total of 70 patients were evaluated, with a median age of 62 years, and 82.8% were male. The majority of patients (72.8%) were diagnosed with extensive-stage (ES) disease. Common symptoms included cough (61.4%), chest pain (45.7%), and breathing difficulty (44.2%). The most commonly used chemotherapy regimen was etoposide-platinum. Overall survival (OS) for all patients was 6.1 months. Three-year OS was significantly better in patients with limited-stage (LS) disease (16.4 months vs. 4.3 months in LS vs. ES disease, p<0.05). Median progression-free survival (mPFS) for all patients was 4 months. Survival rates at 6, 12, 24, and 36 months were 45.7%, 18.5%, 5.7%, and 1.4%, respectively. Median OS was significantly correlated with the number of metastatic sites (8.6 months with <3 organ involvement vs. 1.9 months with ≥3 organ involvement; p<0.0001). Patients who received combined modality treatment had better survival than those treated with chemotherapy alone (10.7 months in chemo-radiotherapy vs. 3 months in chemotherapy alone, p<0.001). Conclusion: SCLC remains a highly aggressive disease with poor survival. Advanced-stage presentation with distant organ metastasis is the most important factor associated with poor survival in patients with SCLC1